Wissensspeicher der Frühen Neuzeit: Formen und Funktionen - Grunert, Frank; Syndikus, Anette (De Gruyter eBook-Paket Literatur- und Kulturwissenschaft, Area Studies, 2015)
With the dissemination of letterpress printing, traditional knowledge stores adapted to changing conditions, resulting in the development of new forms of knowledge acquisition and storage. This book presents the options for knowledge preparation and resultant forms of storage that emerged between 1500 and 1800 from a consistent perspective, examining their intersections and demarcations as well as their constant and transformative elements.